Extending place-specific cultural and artistic identities through creative tourism - Duxbury, Nancy (2021)
The project CREATOUR: Creative Tourism Destination Development in Small Cities and Rural Areas was a national 3,5-year (November 2016 - April 2020) interdisciplinary research-and-application project in Portugal. The project involved five research centres working with 40 participating organizations located in small cities and rural areas across the Norte, Centro, Alentejo, and Algarve regions. Creative tourism offers travellers the opportunity to develop their creative skills and potential through active participation in creative experiences which are characteristic of the place where they are offered. The CREATOUR approach to creative tourism incorporates four dimensions: active participation, learning, creative self-expression, and community engagement. For local agents and organizations involved in CREATOUR, creative tourism provided a new and inspiring lens through which to (re)view and value their territory and local assets, and to reconsider what and how to present to visitors. It also highlighted intangible cultural dimensions as a key part of this picture. The project catalyzed the development and launch of an array of creative tourism offers throughout the four regions, and linked them through the development of a national network. In this process, we found the place that inspired and informed the creative tourism activities, and in which they were designed and implemented, was key to differentiation and development of distinct and meaningful experiences. The project also revealed the issues encountered in start -up situations of creative tourism enterprises in smaller places and sometimes-remote locations. This presentation provides some guidelines and insights from this challenging and inspiring experience.